Georgetown and Leominster account book
Merchant's account book kept in Georgetown, D.C. (1818-1819) and Leominster, Mass. (1792).
Collection material in English.
Keywords: Leominster (Mass.) -- Commerce; Business records -- Massachusetts; Georgetown (Washington, D.C.) -- Commerce; Business records -- Washington (D.C.); Merchants -- Washington (D.C); Merchants -- Massachusetts -- Leominster